2015
DOI: 10.5578/kvj.10408
|View full text |Cite
|
Sign up to set email alerts
|

A Serological Investigation for Bovine Ephemeral Virus Infection in Aydın and Muğla Provinces

Abstract: Bovine Ephemeral Fever (BEF) sokucu sineklerle bulaşan, akut ateş, kaslarda sertlik, topallık, felç, zayıflama ile karakterize rhabdoviral bir hastalıktır. Bu bulgulara bağlı olarak, özellikle süt endüstrisinde önemli kayıplara yol açabilmektedir. Bu araştırmanın amacı, Ege bölgesinde daha önce de görülmüş olan BEF enfeksiyonunun Aydın ve Muğla İllerinde varlığı ve yaygınlığı konusunda veri elde etmektir. Bunun için, süt sığırcılığı işletmelerinden tesadüfi olarak seçilmiş 225 erişkin inekten kan serum örnekle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The serological studies show that, the virus appeared to be circulated in the north and European part of the country (Karaoglu et al, 2007). Reported that, no reported until now of BEFV was obtained from Aegean region located in the west of the country with necessary climate conditions for vectors while a serological study carried out in two provinces in the region found no seropositivity (Erol et al, 2015). The epidemic in 2020 was reported to have started in September in the south and southeast of the country (Karayel-Hacıoglu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The serological studies show that, the virus appeared to be circulated in the north and European part of the country (Karaoglu et al, 2007). Reported that, no reported until now of BEFV was obtained from Aegean region located in the west of the country with necessary climate conditions for vectors while a serological study carried out in two provinces in the region found no seropositivity (Erol et al, 2015). The epidemic in 2020 was reported to have started in September in the south and southeast of the country (Karayel-Hacıoglu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies conducted for the investigation of seroprevalence of BEF in Turkey is limited. In a study conducted to investigate the existence and prevalence of the disease in Aegean region, 125 sera sample from Aydın and 100 from Mugla province, 225 sera samples in total, collected randomly from family-run dairy farms were examined with Blocking ELISA, and none was tested positive for the presence of anti-BEFV antibodies (Erol et al, 2015). The seroprevalence rates in respect of provinces were 2.5% (1/40) in Samsun, 27.5% (11/40) in Amasya and 37.5% (15/40) in Sinop, while no BEFV antibody was found in the samples collected from Tokat and Ordu (Albayrak and Ozan, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The outbreaks of BEF disease seen in 2008 were recorded in Turkey's South-East region as a relatively local outbreaks (Erganiş et al 2010). However, the disease seen in 2012 was detected in some provinces of the Marmara, Aegean and Western Black Sea regions along with the Mediterranean, Central Anatolia, Eastern Anatolia (Alkan et al 2017;Erol et al 2015).…”
Section: Introductionmentioning
confidence: 99%